Towards Equity in Mathematics Education
XVIII, 598 p.
Keywords: The pursuit of equity in mathematics education is an important concern in the history of the present. Since there is no doubt about the significant role of mathematics in almost every aspect of life, it means that all individuals regardless of sex, in any age range, and in whatever context need to be provided with an opportunity to become mathematically able. The publication of his Springer volume on equity in mathematics education is situated at a time when there is strong and sustained research evidence indicating the persistence of an equity gap in mathematics, which has now enabled the mathematics education community to engage in a discourse of access for all. The volume gathers together twenty major chapters that tackle a variety of issues associated with equity in mathematics education along the dimensions of gender, culture, curriculum diversity, and matters of a biological nature. The research studies that are reported and discussed in the volume have been drawn from an international group of distinguished scholars whose impressive, forward-looking, and thought- provoking perspectives on relevant issues incite, broaden, and expand complicated conversations on how we might effectively achieve equity in mathematics education at the local, institutional, and systemic levels. Further, the up-to-date research knowledge in the field that is reflected in this volume provides conceptual and practical outlines for mechanisms of change, including models, examples, and usable theories that can inform the development of powerful equitable practices and the mobilization of meaningful equity interventions in different contexts of mathematics education. .